2017
DOI: 10.1016/j.jhazmat.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rainfall timing and tillage on the transport of steroid hormones in runoff from manure amended row crop fields

Abstract: h i g h l i g h t s• Hormones and metabolites were detected in runoff from test plots fertilized with cattle manure.• Composting can reduce the hormone concentration in manure compared to stockpiling.• About 10% of applied hormones can be lost through the dissolved phase of runoff. a r t i c l e i n f o a b s t r a c tRunoff generated from livestock manure amended row crop fields is one of the major pathways of hormone transport to the aquatic environment. The study determined the effects of manure handling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…It is likely that the shifted sex effect reported by Jeffries et al [89] in male fish collected from these rivers could have been significantly influenced by hormones released from other sources, including crop production and municipal wastewater treatment plants [93]. For example, at detectable concentrations, contaminants from Fusarium-infected grains such as corn, barley, and other small grain crops can contribute to zearalenone concentrations in manure and surface run off [94,95]. Globally, municipal wastewater treatment is arguably the principal source of hormones that are released into the environment, as beef-producing countries that do not use PETs have also reported effects of hormones on aquatic biodiversity [96,97].…”
Section: Environmental Contaminationmentioning
confidence: 94%
See 1 more Smart Citation
“…It is likely that the shifted sex effect reported by Jeffries et al [89] in male fish collected from these rivers could have been significantly influenced by hormones released from other sources, including crop production and municipal wastewater treatment plants [93]. For example, at detectable concentrations, contaminants from Fusarium-infected grains such as corn, barley, and other small grain crops can contribute to zearalenone concentrations in manure and surface run off [94,95]. Globally, municipal wastewater treatment is arguably the principal source of hormones that are released into the environment, as beef-producing countries that do not use PETs have also reported effects of hormones on aquatic biodiversity [96,97].…”
Section: Environmental Contaminationmentioning
confidence: 94%
“…Researchers have shown that composting and stockpiling cattle manure can reduce endogenous hormones in manure. Using composting and stockpiling, a study in the US reported no significant difference in the concentrations of TBA, E, Z, and MGA (average, 19.0 ng/g of dry weight) in manure from cattle that did or did not receive these additives [94]. This group also showed that composting (12.3 ng/g of dry weight) is more effective than stockpiling (25.7 ng/g of dry weight) at reducing hormone concentration in surface water run-off from the feedlot.…”
Section: Environmental Contaminationmentioning
confidence: 99%
“…High intensity of rainfall can threaten water quality, causing landslides, sedimentation, and even flooding (Vannier 2016). According to Biswas et al (2017), the distribution and amount of rainfall greatly affect the occurrence of floods. Rainwater that reaches the ground can become surface runoff and infiltrates the ground (Asdak 2010;Ngongondo et al 2011;Zhang et al 2017).…”
Section: Rainfallmentioning
confidence: 99%
“…Piram et al (2008) even found higher concentrations of FA in effluents compared to influents of a WWTP attributing to GC conjugate hydrolysis. Therefore, these GCs can be released into the soil through untreated wastewater, WWTP effluents, waste activated sludge, pharmaceutical residues, and animal manures (Abdellah et al 2020), causing soils to become significant reservoirs for GCs (Shargil et al 2016). To make matters worse, the GCs accumulated in soil may enter the food chain (Shargil et al 2016).…”
Section: Introductionmentioning
confidence: 99%